Pengaruh Kualitas Pelayanan dan Store Atmosphere Terhadap Kepuasan Pelanggan (Studi Cafe Seis di Kota Medan) - Aisyah, Siti; Aramita, Finta (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to determine and analyze the effect of service quality and Store atmosphere on customer satisfaction (Study of Cafe Seis in Medan City), the research method used in this study used quantitative methods, the population in this study were customers who visited Cafe Seis in unknown quantities. Therefore, the sampling technique used in this study with the Hair et al formula (2014) must be at least four or five times the number of question items. The total questions in this study were 24 questions, so the minimum sample size for this study was 24 x 5 = 120, The data analysis method uses descriptive methods and multiple linear regression analysis with a significant level of 0.05 and gets the results (1) Service Quality variables have a significant effect on Customer Satisfaction This can be seen from the significant value (0.000) < than 0.05 and t-count (2.012) > compared to t-table (1.980). (2) Store atmosphere variables have a significant effect on Customer Satisfaction. This can be seen from the significant value (0.001) < 0.05 and t-count (5.021) > compared to t-table (1,980). (3) Service Quality (X1), and Store atmosphere (X2) simultaneously are significant to Customer Satisfaction.